Charter and Ordinances of the City of Bridgeport: as Amended and Adopted 194, § 1 (1874) - (:unkn) unknown (My University, 1874)
Prohibited the possession, keeping for sale, or for any other purpose within city limits, any quantity of gun powder or gun-cotton exceeding one pound in weight. Also prohibited having, keeping for sale, use, or other purpose, any quantity of nitro-glycerine, or other explosive substances or compounds exceeding six ounces without a special license.
Keywords: GUNPOWDER - STORAGE